Macro- and metabolome-based characterization between gut microbiota and metabolites in patients with colorectal adenomas - Zhili, Guo; Jie, Liu; Peihao, Yin (Frontiers in Microbiology, 2025)
ObjectiveThe gut microbiota has been recognized as a significant regulator in the development and progression of colorectal adenoma (CRA). However, few studies have investigated the presence and association of resident microbial species and metabolites in patients with CRA. Our aim was to analyze differences in gut microbiome composition and metabolites, as well as to evaluate their diagnostic potential for CRA.MethodsWe conducted metagenomic and metabolomic analyses on fecal samples from 90 subjects, including 60 patients with CRA (CRA group) and 30 healthy subjects who served as normal controls (NC group). By integrating fecal metagenomic and metabolomic data, we identified gut microbiota-associated metabolites that showed significant abundance changes in CRA patients. Furthermore, we explored whether these metabolites and microbial species could distinguish CRA patients from healthy individuals.Results16S rRNA gene sequencing and untargeted metabolomics analysis revealed microbial changes that distinguished CRA patients from controls. Microbial population analysis showed that the CRA group formed distinct clusters from the controls, with significant β-diversity (PCA and PCoA analyses, p < 0.05). At the phylum level, the dominant taxa in terms of relative abundance included Firmicutes, Ascomycota, Mycobacteria, Actinobacteria, and Clostridia. Differential analysis of the gut flora based on species abundance revealed significant differences in taxonomic composition between healthy individuals and CRA patients. KEGG functional enrichment analysis indicated that the differential flora were primarily involved in metabolic pathways, including metabolic pathways, biosynthesis of secondary metabolites, microbial metabolism in diverse environments, amino acid biosynthesis, and cofactor biosynthesis. In this study, three microbial species—Fusobacterium mortiferum, Alistipes, and Bacteroides fragilis—were validated as discriminators between healthy individuals and CRA patients, with Alistipes showing higher classification efficacy. Metabolomic analysis revealed differences in tryptophan metabolism, protein degradation products, amides, and phenolic acid metabolites. KEGG enrichment results indicated that metabolic pathways were the most significantly enriched. Differential metabolites were mainly associated with the biosynthesis of plant secondary metabolites. Procrustes and Venn analyses were performed on functional entries of the two omics datasets, highlighting enriched pathways including Metabolic pathways, Glycerophospholipid metabolism, Sphingolipid metabolism, and Alpha-linolenic acid metabolism. A review of the literature confirmed that the differential flora and metabolites are associated with adenoma growth.ConclusionIn this study, metagenomic and metabolomic analyses were conducted in subjects with CRA. The findings based on fecal metagenomic and metabolomic assays suggest that intestinal microecology is altered in CRA patients, leading to changes in gut cellular structure.